AHLI WARIS PENERIMA RADD DALAM PERSPEKTIF FIQIH MAWARIS (FARAIDH) DAN KOMPILASI HUKUM ISLAM (KHI) - Agustina Kumala Dewi (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2016)
Owing to the fact of being a country where Moslem is the majority, it then enables the society to utilize Islamic law. Radd is a bequest distribution problem that affects the remaining properties if all the dzawil furud heirs have obtained their rights. This study aims to know theorem by both scholars and clerics whether they reject radd or receive it. Besides, this paper also will lead reader to comprehend how to deal with Radd according to Islamic Scholar Council and Compilation of Islamic Law, furthermore to understand what kind of Radd concept applied in Indonesia is also going to be explained. As stated by Islamic Scholar Council, Radd solving is to give all dhawil furud with the exception of husband and wife, whereas Compilation of Islamic Law will give all the remaining estate to the beneficiary without any exclusion. Radd concept supposed to be applied in Indonesia is Radd in consideration of kinship in a family since there is transition in responsibility that should be carried out by the heirs’ death without to the neglect of Islamic Scholar Council’s opinion in decission-making.